Brazilian Right: brief outline of historical trajectory in the XX – first quarter of the XXI centuries - Okuneva Liudmila (Латиноамериканский исторический альманах, 2023)
Right-wing parties and movements, as well as right-wing ideology, are an important factor in the political life of Latin American countries. By the end of the second decade of the XXI century. more than half of the political regimes of Latin American countries were right-wing or center-right. In the article, on the example of the analysis of the Brazilian version of the phenomenon of the right trend, an attempt is made to show the reasons for the very existence and political survival of the right and their popularity in society, the deep rootedness of the right ideology in the depths of public consciousness, its influence on public sentiment. A brief analysis of the ideology and politics of right-wing movements and right-wing political leaders is given – from Getúlio Vargas to Jair Bolsonaro.